(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The aspirational constitutionalism brings with it a form of prolixity of socio economic rights. Such prolixity may often lead to a mismatch between the constitutional text and constitutional reality. The judiciary becomes an important player in balancing such mismatch, however without exercise of judicial restraint such balancing has tendency to compromise the traditional concepts of separation of power and democracy. This article seeks to analyze how the trio of Aspirational Constitutionalism, Social Rights Prolixity and Judicial Activism exist in relation to and complement and supplement each other.